Bioremediator Formula for Cultivated Plants Grown on Post-Mining Soil - Syahri, Yolanda Fitria; Mustafa, Marlina; Ratriani, Ratriani (Universitas Panji Sakti, 2025)
Research in the form of bioremediation through Bacillus sp. and VAM tests to degrade nickel and chromium needs to be carried out to obtain the best formula for plant growth. Thus, this research has the following objectives: (1) to obtain the best treatment of soil heavy metal bioremediator (2) to reuse post-mining land into productive land for cultivated plants. The research method will be divided into two activities (1) provision of bioremediator formula and (2) testing of bioremediator formulation on cultivated plants. Based on the study's results, 150 ml Bacillus/plant (A3) has the highest effectiveness in reducing chromium by 0.922% in the soil. While the best formula for reducing nickel is 75 grams of VAM (A6) with a reduction capacity of 0.924%. All treatments on sorghum samples on each chromium and nickel produced values <1, this shows that sorghum only absorbs heavy metals and does not accumulate much of all chromium and nickel heavy metals. Parameters of plant height, number of leaves, wet weight, and dry weight with the DMRT at the α = 5% level showed a very significant effect on the treatment of VAM (A6) 75 grams. Bacillus sp and VAM can be used as a bioremediator agent for cultivated plants planted on post-mining soil.